Characterization Formulation and in Vitro Assesment of Pulsatile Drug Delivery of Montelukast Sodium - Abid Ur Rehman, Gul Hassan, Rahman Shah, Saifullah Khan Khalil, Sameer Ahmad, Amanat Ali, Hikmat Ullah, Qudrat Ullah Khan, Amir Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
The Montelukast pulsatile delivery system was created with the goal of delivering the drug to the colon for successful treatment of nocturnal asthma. The microspheres were sealed within the insoluble hard gelatin capsule body with an erodible hydrogel plug to create a time delayed capsule. Emulsion solvent evaporation was used to make the microspheres. Based on dissolving tests, optimised microsphere formulations were designed. The entire device was enteric coated in order to overcome the variability in gastric emptying time and achieve colon-specific delivery. The hydrogel plug (HPMC K100 and lactose in a 1:1 ratio) with a hardness of 4.5kg/cm2 and a weight of 100 mg was placed in the capsule opening and found to be effective in delaying release of the drug in small intestinal fluid, ejecting the plug into colonic fluid, and releasing the microspheres into colonic fluid after a 5-hour lag time. Three dissolving medium with pH 1.2, 7.4, and 6.8 were employed consecutively to imitate pH fluctuations along the GI tract. The medication and polymer had no interaction, according to the FTIR analysis. Montelukast microspheres 1:4 ratio had the longest release time of all the formulations, lasting 12 hours. The results showed that the device is capable of delaying drug release for a programmable period of time and treating asthma. Keywords: Montelukast, hydrogel plugs, pulsatile delivery, nocturnal asthma, microspheres.